Disentangling Ecological Restoration's Impact on Terrestrial Water Storage - Xiaofan Shen; Liantao Niu; Xiaoxu Jia; Ting Yang; Wei Hu; Chaoyang Wu; Jiangdong Chu; Asim Biswas; Ming'an Shao (Geophysical Research Letters)
Abstract Large‐scale ecological restoration (ER) in semiarid regions is often associated with substantial terrestrial water storage (TWS) depletion. This study challenged previous estimates by demonstrating the critical importance of considering other human activities when assessing ER impacts on TWS. Using a novel analytical framework integrating GRACE satellite data and ground observations, we analyzed TWS changes in China's Mu Us Sandyland under two scenarios: with and without considering mining and farming activities. Our results show that ER consumed TWS at an average rate of 11.7 ± 12.2 mm yr−1 from 2003 to 2022. Neglecting the impacts of mining and farming led to a 251% overestimation of ER's effect on TWS. This study provided a more nuanced understanding of water resource dynamics in restored ecosystems, emphasizing the need for comprehensive approaches in TWS assessments and informing sustainable land management strategies globally.